Digital transformation of ornamental plant businesses in Batu City through TikTok live - Fitra Ayu Adira; Hari Wahyono; Hadi Sumarsono (Pusat P2M Politeknik Negeri Batam, 2026)
Research on digital transformation in small and medium-sized enterprises generally focuses on the use of social media in general, while studies that specifically examine the adaptation process through live streaming features, especially in the local ornamental plant business, are still limited. In addition, the subjective experiences of business actors in facing the process of learning and adapting to technology have not been widely studied. Based on these gaps, this study aims to analyze the digital adaptation process in the development of ornamental plant businesses in Batu City through the use of TikTok Live as a marketing medium. This study uses a qualitative approach with a phenomenological method. Theoretically, this study uses Everett Rogers' Diffusion of Innovation, Fred Davis' Technology Acceptance Model (TAM), and Herbert A. Simon's Behavioral Economics perspective to explain the process of adoption, acceptance, and decision-making in the use of technology. The informants consisted of five business actors who actively use TikTok Live. Data was collected through in-depth interviews, observation, documentation, and snowball sampling techniques, then analyzed through data organization, thematic coding, and conclusion drawing. The results show that before using TikTok Live, business owners still relied on traditional marketing with limited reach. The digital adaptation process involved increasing digital literacy, content creativity, and direct interaction with consumers. After utilizing this feature, informants experienced an increase in market reach, consumer interaction, and potential income. However, there were obstacles in the form of limited digital literacy, suboptimal technological infrastructure, and a lack of external assistance. This study contributes by providing an empirical description of the digital adaptation strategies of ornamental plant businesses, which can be used as a reference in facing digital transformation.